Implications of secondary DNA transfer & public perceptions on the national DNA database of South Africa - Mokoma, Polo M. (University of the Free State, 2017)
Abstract not available
Dissertation (M.Sc. Forensic Genetics (Genetics))--University of the Free State, 2017
Keywords: DNA data banks -- South Africa; Criminal investigation; Forensic genetics